Nietzsche. - Schacht, Richard (Arguments of the philosophers., 1985)
Few philosophers have been as widely misunderstood as Nietzsche. His detractors and followers alike have often fundamentally misinterpreted him, distorting his views and intentions and criticizing or celebrating him for reasons removed from the views he actually held. Now Nietzsche assesses his place in European thought, concentrating upon his writings in the last decade of his productive life.